EFFECT OF TEACHING ON SELF CARE ABILITY OF PATIENTS WITH ILEOSTOMY AND COLOSTOMY - Sadeghi sanabadi; Koocheki, SA; Solieman borogerdi; Mohammad alyha; Khachian, A; Hoseini, F (Iran University of Medical Sciences, 2003)
Teaching the patients is considered to be an important duty of nurses, and is one of the standards of quality nursing supervisions, According to this, all patients have the right to be thought in order to keep their health. Suffering from a chronic illness, Patients with ostomies need to gain the knowledge and skill of being self care. So, determing the effect of teaching on self care manner of patient with an ostomy, a clinical trial study was conducted. Contributers were 32 patients selected by continuous and random method. All patients were interviewed before teaching and then teaching booklets were distributed. Findings revealed that There was not a meaningful difference between patient's refferal to physician due to any unpredicted signs or compliance of diet regime in prevention of constipation, but comparatively, after teaching a significant relationship was found between prevention of bad odor, diarrhea, stenosis of the ostoma and the correct way of irrigation and changing of the bag (p<0.05). Moreover, we found that 67.7% of the patients complained about the bad odor of the stoma, 41.9% of them claimed that they could not do exercises, 54.8% said that their ostomies interfere with their social life, 53.1% did not know that there is an institution to help them, and finally 56.3% reckoned that they had not had knowledge about their stoma and the way to take care of it. Since, the results highlighted the effectiveness of teaching in improving self care ability, serious and organized teaching programs is suggested to be performed by nurses.